2011
DOI: 10.1371/journal.pcbi.1002073
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Ortholog Conjecture with Comparative Functional Genomic Data from Mammals

Abstract: A common assumption in comparative genomics is that orthologous genes share greater functional similarity than do paralogous genes (the “ortholog conjecture”). Many methods used to computationally predict protein function are based on this assumption, even though it is largely untested. Here we present the first large-scale test of the ortholog conjecture using comparative functional genomic data from human and mouse. We use the experimentally derived functions of more than 8,900 genes, as well as an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
234
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(251 citation statements)
references
References 53 publications
14
234
3
Order By: Relevance
“…This result is consistent with Chen and Zhang study [32]. The plots of expression similarity measured using linear or rank correlation coefficients were qualitatively similar to the analogous plots reported by Nehrt and colleagues [26] (Figures 1(c) and 1(d)) in that the strongest correlation was observed among within-species paralogs, followed by orthologs and then by between-species paralogs. For the between-species paralogs, significant expression similarity was observed only at low sequence divergence whereas at higher divergence, the correlation coefficient values were much lower (Figures 1(c) and 1(d)).…”
Section: Ortholog Conjecture and Gene Duplicationssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with Chen and Zhang study [32]. The plots of expression similarity measured using linear or rank correlation coefficients were qualitatively similar to the analogous plots reported by Nehrt and colleagues [26] (Figures 1(c) and 1(d)) in that the strongest correlation was observed among within-species paralogs, followed by orthologs and then by between-species paralogs. For the between-species paralogs, significant expression similarity was observed only at low sequence divergence whereas at higher divergence, the correlation coefficient values were much lower (Figures 1(c) and 1(d)).…”
Section: Ortholog Conjecture and Gene Duplicationssupporting
confidence: 91%
“…They further showed that (iii) functional and expression similarities between orthologs are independent of the protein sequence identity between the orthologs. These results are inconsistent with the OC hypothesis, prompting Nehrt and coworkers to propose that the primary determinant of the evolutionary rate of gene function and expression is a cellular context in which the genes act [26]. This “cellular context” hypothesis could explain why within-species paralogs were observed to be more similar in function and expression than between-species paralogs and orthologs [26].…”
Section: Ortholog Conjecture and Gene Duplicationsmentioning
confidence: 99%
“…3 ; [ 34 ]). functional similarity of orthologs (genes related through speciation) across different species and paralogs (genes related through duplication) within the same species, and observed a much higher level of functional conservation among the latter [ 36 ]. However, this difference was almost entirely due to the fact that the GO functional annotations of same-species paralogs are ~50 times more likely to be derived from the same paper than orthologs; when controlling for authorship and other biases, the difference in functional similarity between same-species paralogs and orthologs vanished and even became in favor of orthologs [ 34 ].…”
Section: Biases Associated With Particular Evidence Codesmentioning
confidence: 99%
“…A general assumption is that orthologous genes usually have equivalent biological functions in different organisms (Dolinski and Botstein, 2007). However, this assumption has been challenged by evidence of divergence between human and mouse orthologs (Ginis et al, 2004;Liu et al, 2010Liu et al, , 2011Nehrt et al, 2011;Yashiro et al, 2000). To correctly use mouse genes to understand the normal and pathological functions of their human orthologs, more research is required to assess genome-wide similarities and discrepancies between human-mouse orthologs (Gabaldon and Koonin, 2013;Studer and Robinson-Rechavi, 2009).…”
Section: Introductionmentioning
confidence: 99%